2013
DOI: 10.1111/j.1365-4632.2012.05849.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sporotrichosis in Venezuela

Abstract: Sporotrichosis is an endemic subcutaneous mycosis in Venezuela. There are no reports to this date of disseminated forms of the disease, even amongst patients with acquired immunodeficiency syndrome. Direct microscopic examination of wet mount slides with saline solution or distilled water in the search for asteroid bodies is paramount. Saturated sodium and potassium iodine solutions continue to be extremely efficacious and affordable to most of our patients, therefore our treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
7
22
0
Order By: Relevance
“…In our study, we found that, among the subcutaneous mycoses found in Peru, sporotrichosis was the most common and mainly located throughout highlands of Peru (Apurimac, Cajamarca, La Libertad, and Cusco). There is little doubt that sporotrichosis remains a major cause of morbidity in developing nations, such as Peru, Mexico, Brazil, Colom‐bia, and Venezuela, and our study here of sporotrichosis in Peru confirms the known distribution of sporotrichosis as well as the geographical areas where sporotrichosis has historically been a health problem. Therefore, healthcare providers should remain alert to the possibility that sporotrichosis may occur in 13 geographic foci in Peru, particularly in the regions of Apurimac, Cajamarca, La Libertad, and Cusco.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, we found that, among the subcutaneous mycoses found in Peru, sporotrichosis was the most common and mainly located throughout highlands of Peru (Apurimac, Cajamarca, La Libertad, and Cusco). There is little doubt that sporotrichosis remains a major cause of morbidity in developing nations, such as Peru, Mexico, Brazil, Colom‐bia, and Venezuela, and our study here of sporotrichosis in Peru confirms the known distribution of sporotrichosis as well as the geographical areas where sporotrichosis has historically been a health problem. Therefore, healthcare providers should remain alert to the possibility that sporotrichosis may occur in 13 geographic foci in Peru, particularly in the regions of Apurimac, Cajamarca, La Libertad, and Cusco.…”
Section: Discussionsupporting
confidence: 78%
“…Sporotrichosis is an endemic mycosis in some regions of the world [4][5][6][7][8]. Moreover, it has re-emerged in recent years with distinct patterns of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in 1935, nevertheless the exact prevalence in the country is unknown [24]. According to conventional mycological procedures, as well as epidemiological data, all isolates related to sporotrichosis have been identified as Sporothrix schenckii .…”
Section: Introductionmentioning
confidence: 99%